2014
DOI: 10.2298/vsp130722045n
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma risk prediction models

Abstract: Application of different models for risk assessment and prediction of melanoma should provide efficient and standardized tool in the hands of clinicians. The presented models offer effective discrimination of individuals at high risk, transparent decision making and real-time implementation suitable for clinical practice. A continuous melanoma database growth would provide for further adjustments and enhancements in model accuracy as well as offering a possibility for successful application of more advanced da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We included 42 studies in our TRIPOD rating. Forty studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were adopted from the systematic review about risk prediction models for melanoma published in 2020, whereas the remaining two studies [ 60 , 61 ] arose from the updated literature search. Details on the information extracted from the studies are summarized in Table A1 .…”
Section: Resultsmentioning
confidence: 99%
“…We included 42 studies in our TRIPOD rating. Forty studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were adopted from the systematic review about risk prediction models for melanoma published in 2020, whereas the remaining two studies [ 60 , 61 ] arose from the updated literature search. Details on the information extracted from the studies are summarized in Table A1 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, we included 42 studies in our PROBAST rating. Forty studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] were adopted from the most recent systematic review about risk prediction models for melanoma that was published in 2020. The remaining two recent studies [ 62 , 63 ] were identified through the updated literature search.…”
Section: Resultsmentioning
confidence: 99%
“… + - - Stefanaki et al [ 56 ] D 2013 Case-control - ? + - - Nikolic et al [ 49 ] D 2014 Case-control - ? + ?…”
Section: Table A1mentioning
confidence: 99%
“…Demographic Information of the Participants use, wearing sleeved clothing, being in the shade, skin color, skin assessment in terms of cancer, age, sex and ethnicity were investigated as data elements about melanoma [15]. Also, another study conducted by Nikolic and et al, to identify the most important factors affecting on melanoma in the population showed that factors such as Sex, age, education level, medical history, melanoma in the family (first degree relatives), exposure to ultraviolet rays, use of sunscreens, sunburn, hormonal contraceptive treatment (HCT) and immunosuppressive treatment have been identified as important data elements in this regard [16]. In the study of Green et al, with the aim of investigating the effect of sunscreen cream in dealing with melanoma, elements such as gender, age, observation of skin cancer, reaction to sunlight, color, occupation, number of sunburn and birthmark observation were considered as data elements [17].…”
Section: Discussionmentioning
confidence: 99%